Решить уравнение: lg(x^2-8)=lg(2-9x)

Vasianeumaha Vasianeumaha    1   31.07.2019 11:00    10

Ответы
Dancerebuclic2017 Dancerebuclic2017  28.09.2020 15:01
Х² - 8 = 2 - 9х
х² + 9х -10 = 0
D = 9² - 4·1·(-10) = 81 + 40 = 121; √121 = 11
x1 = (-9 - 11)/2 = -10
x2 = (-9 +11)/2 = 1
Проверка:
если х = -10, то имеем lg((-10)² - 8) = lg(2 - 9·(-10)) или lg92 = lg92 - верно
при х = 1 имеем:  lg(1² - 8) = lg(2 - 9·1) или lg(-7) = lg(-7) - не имеет смысла, т.е.  х = 1 - посторонний корень
ответ: -10.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра